Pregnancy Risks of Young Mothers in Medical Discourse and Cultural Settings - Anisa Puspa Rani; Heru Nugroho; Desintha Dwi Asriani (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2023)
East Lombok Regency, despite implementing pregnancy health programs, grapples with a persistently high pregnancy risk. This study investigates the disparity between medical and Sasak cultural perspectives on young mothers’ pregnancy risks. Qualitative case study research reveals a conflict between community sociocultural narratives and medical viewpoints. Cultural norms normalize medical narratives, shaping pre-marital reproductive arrangements, body perceptions, and idealized pregnancy concepts. Young mothers, influenced by cultural values, accept pregnancy as a collective social process within the family. The study emphasizes the impact of cultural determinism on shaping perceptions and preferences for young mothers’ pregnancy health, highlighting the need for an integrated approach that bridges medical and cultural perspectives to address and mitigate pregnancy risks effectively.